2006
DOI: 10.1007/s10714-006-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state for anisotropic spheres

Abstract: We present a new class of exact interior solutions for anisotropic spheres to the Einstein field equations with a prescribed energy density. This category of solutions has similar energy density profiles to the models of Chaisi and Maharaj (Gen. Rel. Grav. 37, 1177-1189) whose approach we follow in the integration process. A distinguishing feature of the solutions presented is that they satisfy a barotropic equation of state linearly relating the radial pressure to the energy density. Keywords Anisotropic rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Secondly, we choose an EOS which linearly relates the radial pressure to the energy density. Maharaj & Chaisi (2006) have demonstrated that this simple EOS is consistent in the modelling of compact matter such as neutron stars and quasi‐stellar objects. The EOS yields values of surface redshifts and masses that correspond to realistic stellar objects such as Her X‐1 and Vela X‐1 (Gokhroo & Mehra 1994; Chaisi & Maharaj 2005).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Secondly, we choose an EOS which linearly relates the radial pressure to the energy density. Maharaj & Chaisi (2006) have demonstrated that this simple EOS is consistent in the modelling of compact matter such as neutron stars and quasi‐stellar objects. The EOS yields values of surface redshifts and masses that correspond to realistic stellar objects such as Her X‐1 and Vela X‐1 (Gokhroo & Mehra 1994; Chaisi & Maharaj 2005).…”
Section: Introductionmentioning
confidence: 56%
“…Our analysis depends critically on the choice of the mass function given by so that a linear EOS is possible. Note that some other treatments, such as the result of Maharaj & Chaisi (2006), with a linear EOS has the unrealistic feature of vanishing energy density at the boundary. Our model does not suffer from this defect.…”
Section: Discussionmentioning
confidence: 99%
“…which is very simple. In more general form it was used in the past, [56], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81]. In the context of conformal flatness it was used in [40], Example 4, and [42], model III but only a partial physical analysis has been done.…”
Section: The Modelmentioning
confidence: 99%
“…Linear EoS is consistent in the modeling of compact objects, one can achieve modeling of anisotropic spherical objects with quark matter distributions [74,75]. It is suitable in retrieving the mass-radius relationship and values of surface redshifts corresponding to realistic stars [76,77]. For envelope region, we assume the same anisotropic Tolman VII [61] with linear EoS…”
Section: The Core-envelope Modelmentioning
confidence: 99%